Լիբանանի կրոնա-համայնքային համակարգը - Հարությունյան, Լիլիթ («Զանգակ - 97»)
The paper deals with ihe Lebanese confessional political systcm, which has become an oddity in the Arab world. Lebanon consists of several Christian and Muslim communities: the Maronite, the Greek Orthodox, the Greek Catholic, the Amienian, the Sunni, the Shi'i, the Druze and etc. In the unwritten National Pact of 1943, the major religious communiües reached a compromise accord tliat proved thus far impervious to modification. Under the arrangcment, the President of the Republic must always be a Maronite, the prime-minister a Sunni Muslim, and the President of the Parliament a Shi i Muslim. The apportionment of deputies in the Parliament rests on an immutable numerical formula for sectarian representation, five Christians to every five non-Christians. The President of Lebanon will make use of his real power if he is in military alliance with the Muslim leaders.
Keywords: Կրոն; Պատմություն